The Impact of Management Skills of Agricultural Entities in Relation to Economic Efficiency and Natural-Climatic Conditions in Slovakia - KOTULIČ, Rastislav; ADAMIŠIN, Peter; VOZÁROVÁ, Ivana KRAVČÁKOVÁ; VAVREK, Roman (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017, 2017)
affects the production orientation and the effectiveness of the agri-food sector. The aim of this paper is to evaluate the development in the categorization of agricultural plots by the regional differentiation of Slovakia at the NUTS IV level (districts) and draw attention to probable development of differentiation of districts in primary agricultural production in Slovakia, while ensuring the sustainability of the economic performance of the given sector. On the basis of completed analysis, we can conclude that natural and climatic conditions have a dominant influence on achievable productivity and economic efficiency of the agricultural entities in ensuring the sustainability of the economic performance of agriculture in different regions of Slovakia.